Preliminary experience with intravenous gadoxetate disodium as a craniospinal MR contrast agent. Issue 12 (December 2015) - McKinney, Alexander M.; Gawande, Rakhee; Pezeshk, Parham; Truwit, Charles L.; Rykken, Jeffrey B.
Highlights: Gadoxetate disodium may be an alternative gadolinium-based contrast agent (GBCA) in both non-renally impaired and renally impaired patients. Gadoxetate disodium is partially (50%) excreted by the liver. Gadoxetate disodium was utilized as the alternative GBCA, and was able to direct therapy or surgery in several patients. Abstract: Introduction: Gadoxetate disodium is a gadolinium-based contrast agent (GBCA) typically used for body imaging, as about 50% of its excretion is via the liver. Its use for craniospinal MRI has not been reported. Materials and methods: Over a 3 years period, 31 adults underwent postcontrast MRI using gadoxetate disodium, each of whom had a relative contraindication to a GBCA, but a GBCA was deemed necessary by the clinical service to direct therapy. Postcontrast T1WI included either gradient-echo (GET1WI, n  = 12) or spin-echo (SET1WI, n  = 13) imaging. The contraindication in 29 patients was stage 3–5 chronic kidney disease (CKD) or acute kidney injury (AKI); the other two had normal kidney function, but a history of a reaction to another GBCA (vomiting in one and hypersensitivity in the other). Over a 3 years period, in those patients in whom a GBCA was both deemed necessary and had an estimated GFR (eGFR) of <40 ml/min/1.73 m 2 (i.e., stage 3–5 CKD), both informed consent and nephrology consultation was obtained. A 10 ml dose was given for cranial ( n  = 23), spinal ( n  = 9), and neck/face MRI ( n  = 3), as well as craniocervical MRA ( n  = 6). Three neuroradiologists separately evaluated for normal enhancement in 11 structures. The contrast enhancing percentage (CE%) was measured in 3 structures, and in enhancing lesions, if present. Results: The pre-MRI eGFR was not significantly different from that at 30–90 days ( p  = 0.522) in the 23 patients with an available eGFR at >90 days post-MRI; no patients developed acute kidney injury post-MRI, nor nephrogenic systemic fibrosis. Of the 11 intracranial structures scored, the superior sagittal sinus, pituitary stalk, and atrial choroid plexus enhanced in all 23 patients who underwent brain MRI, with CE%'s of 171.0%, 73.0%, and 69.8%, respectively. The number of patients with enhancing lesions were 3/23 brain MRI's, 8/9 spinal MRI's, 3/3 neck MRI's, and 2/6 craniocervical MRA/MRV's. In 9 spinal MRI's, the basivertebral plexus CE% was 213.7%; in the 7 with spondylodiscitis, the CE% measured 125.8% in enhancing epidural tissue, with a contrast-to-noise ratio (CNR) of 98.0%. Conclusion: This preliminary report describes the use of gadoxetate disodium as an alternative GBCA for craniospinal MRI and MRA in the renally impaired, but its efficacy in this regard must be further evaluated prospectively.